Efficient spin-orbit torque magnetization switching by reducing domain nucleation energy - Jin, Tianli (2022)
Spin-orbit torque (SOT) induced magnetization switching occurs via either coherent switching for devices with sizes comparable to a single domain, or domain nucleation followed by domain wall (DW) propagation for the larger devices. This study reveals that the energy required in domain nucleation is up to five times higher than DW propagation to achieve magnetization switching for any device smaller than 100 nm. Hence, the minimization of the domain nucleation energy is critical to the optimization of energy efficiency. The reduction in domain nucleation energy is demonstrated in this work using an external magnetic field and the Dzyaloshinskii–Moriya interaction. Lastly, to capitalize on the energy difference between domain nucleation and DW propagation, we propose a two-pulse scheme that utilizes a brief high-power pulse to initiate domain nucleation followed by a longer low-power pulse for DW propagation. The two-pulse scheme can achieve energy savings of up to 72% compared to using a single-pulse scheme. Our result determines that the two-pulse scheme has strong potential for significant improvements in SOT switching energy efficiency.